GAME-BASED MOBILE APPLICATION (P-KSSMPKPS) REMEDIAL INSTRUCTION IN FRACTION LEARNING: BEST PRACTICES TO TEACHING AND LEARNING PERFORMANCE ON STUDENTS WITH LEARNING DISABILITIES - Murugesu Supermaniam; Rozniza Zaharudin, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
This research was carried out to investigate the efficacy of the creative game-based mobile learning application (P-KSSMPKPS) in addressing students with learning disabilities in the discipline topic. A total of 152 students from ten different schools in the South Kinta district in Perak, Malaysia, divided into experimental group and control groups were used: (1) traditional teaching methods, (2) as the best instructional case we could implement, teaching with a mobile game-based learning application (P-KSSMPKPS) who had participated in this survey. The study was conducted based on the mixed experimental design in which each respondent was given pre-test, treatment, and post-test. The mobile application developed is a treatment method used due to its educational advantages that impact long-term memory. The development of this mobile application incorporates multimedia and visual elements that enable the attention of disadvantaged students to explore and follow the learning process through to the end of learning. This mobile application has been implemented and tested for its effectiveness on student achievement after learning for a fraction of mobile apps developed. As a result of this mobile application, it was found that student achievement improved and resolved further errors in the students. These results open a new performance enhancement using creative fraction (P-KSSMPKPS) game-based learning as remedial instruction to students with learning problems.